The stalking horse - Monfredo, Miriam Grace (New York : Berkley Prime Crime, 1999)
A fictional account of the Pinkerton Detective Agency's involvement in uncovering the Baltimore Plot, an assassination attempt on Abraham Lincoln in 1861.
Publisher's Weekly
School Library Journal
Wilson's Fiction
Adult
Adult
Keywords: Tryon, Glynis (Fictitious character) -- Fiction; Women librarians -- New York (State) -- Seneca Falls -- Fiction; Historical fiction; Mystery fiction; Tryon, Glynis (Fictional character) -- Fiction; Women librarians -- Fiction; United States -- History -- Civil War, 1861-1865 -- Fiction; United States -- History -- 1861-1865, Civil War -- Fiction